Multiple sensor theory in cardiovascular mechanosensory units - Yu, Jerry (Frontiers in Physiology, 2023)
Multiple sensor theory (MST) has advanced our understanding of how lung mechanosensors operate. That is, single lung units contain multiple homogeneous or heterogeneous sensors. Each detects sensor-specific mechanical information and interacts with other sensors lying within the unit sending integrated information to the brain to evoke reflexes. MST explains numerous controversial issues in the respiratory system. Recent studies in baroreceptors (BRs), along with reinterpretation of recordings appearing in the literature, indicate MST also operates in the cardiovascular (CV) system. This review outlines evidence supporting MST in the CV system and provides examples to apply the theory. Longstanding controversies surrounding the CV sensors are also considered.